Curcuminoid Analogs Differentially Modulate Nuclear Factor Kappa-Light-Chain-Enhancer, P65 Serine276, Mitogen- and Stress-activated Protein Kinase 1 And MicroRNA 148a Status. Issue 3 (August 2019) - Cavaleri, Franco
Abstract : Background: Curcumin has been used successfully to treat inflammatory conditions; however, reliability and repeatability of clinical and bench research results have been a challenge. Curcumin is comprised of 3 curcuminoid analogs that can vary in proportion from one extract to another, even from batch to batch from the same commercial supplier. A better understanding of how each curcuminoid analog comprising the curcumin extract can partake in the overall curcumin pharmacology might give us better insight on the polypharmacology involved. Methods/Results: Applied as pretreatment drugs, all 3 curcuminoids, curcumin I (diferuloylmethane), curcumin II (demethoxycurcumin), and curcumin III (bisdemthoxycurcumin), are shown here to modulate 3 key subcellular drug targets differentially. Nucleotranslocation by the curcuminoids is not apparent in the lipopolysaccharide-induced BV2 (immortalised murine microglial cell line) cells. At a nuclear level, multiple compounding findings related to curcumin pharmacology, regulate transactivation of the Nuclear Factor kappa-light-chain-enhancer (NF-kB) heterodimer once it has translocated. Each of the 3 curcuminoid analogs seems to inhibit phosphorylation of p65 (REL-associated protein involved in NF-κB protein formation) at residue serine 276 of the transcription factor's transactivation domain with curcumin I showing a significant hindrance. On the other hand, curcumin III and not curcumins I or II is found to significantly downregulate mitogen- and stress-activated protein kinase 1 status in both the cytosol and the nucleus of these cells. The upstream mechanism repressing mitogen- and stress-activated protein kinase 1 status is also shown to be the upregulation of MIR 148a by curcumin III. Curcumin II shows downregulatory activity of microRNA (MIR) 148a in opposition to curcumin III's upregulatory activity; whereas curcumin I remains neutral with regards to this target. Conclusions: These results demonstrate that although there are some common targets and biochemical activity by the curcuminoid analogs, a differential activity by each can also be observed on other targets. These new findings show us that the common curcumin extract can be utilized with greater selectivity against specific drug targets and the associated disease pathologies. It also demonstrates the importance of establishing a standardization process that takes into account these curcuminoid proportions with the objective of improving reliability of pharmacology and repeatability of research outcomes.